Faktor- Faktor Yang Berhubungan Dengan Kejadian Preeklamsia Pada Ibu Hamil Trimester III Di Rumah Sakit Umum Daerah Kota Depok - Nur Handayani (Politeknik Karya Husada, 2022)
Factors Affecting Preeclampsia in Third Trimester Pregnant Women at the Depok City Hospital in 2020. Preeclampsia/eclampsia is a complication of pregnancy and childbirth characterized by increased blood pressure, proteinuria and edema, which are sometimes accompanied by complications leading to coma. determine the factors associated with the incidence of severe preeclampsia in third trimester pregnant women. The design used in this research is descriptive analytic by using secondary data which is carried out through a cross sectional approach to determine between the independent variables (age, parity, history of hypertension, education, occupation, and gemelli) and the dependent variable (preeclampsia). The results of this study found that pregnant women with preeclampsia experienced severe preeclampsia (62.4%), mild preeclampsia (37.6%). The results of the analysis of the p-value of 0.005 regarding the incidence of preeclampsia in third trimester pregnant women at Depok City Hospital in 2020, namely that there is a significant relationship between age with a p-value of 0.000, parity with a p-value of 0.000, and history of hypertension with a p-value of 0.004. There is no significant relationship between education with a p-value of 0.882, employment with a p-value of 0.349 and gemelli with a p-value of 0.669.